GAMIFIED LEARNING IN SPEAKING CLASS: INVESTIGATION OF OUTCOMES AND STUDENTS’ FEEDBACK AT TENTH GRADE STUDENTS OF SMAN 1 KOTA BENGKULU - Vera Dwi Putri (STKIP Subang, 2026)
This study aims to analyze the effect of game-based learning (gamified learning) on improving eighth-grade students' speaking skills in English lessons at SMAN 1 Bengkulu City and to determine students' perceptions of the method's implementation. This study used a mixed-methods approach by combining quantitative and qualitative data. Quantitative data were obtained through speaking tests (pre-test and post-test) and questionnaires with 20 Likert scale statements, while qualitative data were collected through semi-structured interviews and classroom observations. The pre-test results showed an average student score of 50.33 with a dominant category of